ON THE ENERGY OF COSMIC RADIATION ALLOWED BY THE EARTHS MAGNETIC FIELD - SANDOVAL VALLARTA, MANUEL (UNIVERSIDAD NACIONAL AUTONOMA DE MEXICO, INSTITUTO DE FISICA, CD. MEXICO, DF, MEX, 1950)
Curves giving proton energies (a) below which no energy is allowed by the earth's magnetic field, (b) above which all energies are permitted, for all latitudes in case (a), for latitudes from 0° to 40° geomagnetic in case (b), are given for the following
PHYS REV D
Keywords: ENERGY, COSMIC RADIATION, ALLOWED, EARTHS MAGNETIC, FIELD; MULTIDISCIPLINARIA; ELECTROMAGNETISMO; MAGNETISMO